A systems thinking framework to improve care of the terminally ill: An Australian case study - Elizabeth Summerfield (The Beryl Institute, 2020)
This paper argues the value of systems thinking to patients, family members and medical practitioners in end-of-life care, particularly as a mechanism for considering when palliative care should be introduced as preferred treatment. It applies a well-established set of tenets in systems thinking retrospectively to a case study of patient care in Australia. This highlights how and where different decisions might have been made, based on a holistic consideration of the patient's best interests. The case is written from the perspective of a family caregiver. It argues that early, deliberate conversation, framed by systems thinking tenets, can support the call for the more timely intervention of palliative care. As a precursor to effective conversation, the case supports recent calls for increased training in systems thinking in graduate and continuing medical education. A change in medical practice would both facilitate and be enabled by a broader cultural change in public attitudes toward dying, end-of-life care and death. Encouraging the documentation of single case studies, written or co-written by medical practitioners and family carers can contribute to the evidence base of both medical and public education. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens